Assessment of Variations in Mandibular Cortical Bone Thickness with Its Density and Their Correlation with Age and Gender - A Cone Beam Computed Tomography Study - T. K. Zubaida Musaina; Prathima Shetty; Prashanth Shenoy; Lakshmikanth Chathra; K. M. Veena; Rachana Prabhu (Wolters Kluwer Medknow Publications, 2024)
Background: Osteoporosis is a skeletal disorder characterized by a decreased bone density and increased risk of fractures. It often develops silently, with individuals unaware of its presence until a fracture occurs. Insights into age-related changes and gender can aid in early diagnosis and management of bone loss conditions, like osteoporosis and other bone-related conditions. Objective: To assess the cortical bone thickness and density of the mandible using cone beam computed tomography (CBCT), to compare the cortical bone thickness and density in different gender groups, and to compare the cortical bone thickness and density in different age groups. Methodology: A retrospective study was done in the Department of Oral Medicine and Radiology from the archives based on inclusion and exclusion criteria. The study included 162 patients (81 males and 81 females). Each gender group was divided into three sub-groups based on the age. CBCT scans were obtained, and evaluation of the cortical bone for its density and thickness was performed at three points. Three points were marked at the equidistance of 10 mm starting from the mental foramen posteriorly: P1, at the level of mental foramen; P2, 10 mm distance from P1; and P3, 10 mm distance from P2. In the cross section in each level, buccal, lingual, and inferior measurements of mandibular cortical bone thickness and density were done at the level of the inferior alveolar canal at these three points. Collected data were subjected to statistical analysis. Results: Cortical bone thickness showed greater values in male patients compared to female patients. Mandibular cortical thickness and density values were significantly higher in the first age group (20-40 years) than in the older age group (>60 years). P <0.05 and was statistically significant. Conclusion: The results of this study show that there is alteration in mandibular cortical bone thickness and density with different ages and gender groups.